Comparison of mini-percutaneous nephrolithotomy and retroperitoneal laparoscopic ureterolithotomy for treatment of impacted proximal ureteral stones greater than 15 mm - Guo-Liang Lu; Xiao-Jin Wang; Bao-Xing Huang; Yang Zhao; Wei-Chao Tu; Xing-Wei Jin; Yuan Shao; Da-Wei Wang; Yuan-Yuan Ji (Chinese Medical Journal, 2021)
Abstract. Background:. The optimal treatment for large impacted proximal ureteral stones remains controversial. The aim of this study was to evaluate the efficacy, safety, and potential complications of mini-percutaneous nephrolithotomy (MPCNL) and retroperitoneal laparoscopic ureterolithotomy (RPLU) in the treatment of impacted proximal ureteral stones with size greater than 15 mm. Methods:. A total of 268 patients with impacted proximal ureteral stones greater than 15 mm who received MPCNL or RPLU procedures were enrolled consecutively between January 2014 and January 2019. Data on surgical outcomes and complications were collected and analyzed. Results:. Demographic and ureteral stone characteristics found between these two groups were not significantly different. The surgical success rate (139/142, 97.9% vs. 121/126, 96.0%, P = 0.595) and stone-free rate after 1 month (139/142, 97.9% vs. 119/126, 94.4%, P = 0.245) of RPLU group were marginally higher than that of the MPCNL group, but there was no significant difference. There was no significant difference in the drop of hemoglobin between the two groups (0.8 ± 0.6 vs. 0.4 ± 0. 2 g/dL, P = 0.621). The mean operative time (68.2 ± 12.5 vs. 87.2 ± 16.8 min, P = 0.041), post-operative analgesics usage (2/121, 1.7% vs. 13/139, 9.4%, P = 0.017), length of hospital stay after surgery (2.2 ± 0.6 vs. 4.8 ± 0.9 days, P < 0.001), double J stent time (3.2 ± 0.5 vs. 3.9 ± 0.8 days, P = 0.027), time of catheterization (1.1 ± 0.3 vs. 3.5 ± 0.5 days, P < 0.001), and time of drainage tube (2.3 ± 0.3 vs. 4.6 ± 0.6 days, P < 0.001) of MPCNL group were significantly shorter than that of the RPLU group. The complication rate was similar between the two groups (20/121, 16.5% vs. 31/139, 22.3%, P = 0.242). Conclusions:. MPCNL and RPLU have similar surgical success and stone clearance in treating impacted proximal ureteral stones greater than 15 mm, while patients undergoing MPCNL had a lower post-operative pain rate and a faster recovery.